Stock Market Dispersion, Sectoral Shocks, and the German Business Cycle - Jörg Döpke; Christian Pierdzioch (Kiel Institute of World Economics (IfW), 2000)
This paper elaborates on the relative importance of sectoral shocks for real economic activity in Germany. Implications of multisectoral real business cycle models are examined by resorting to testing techniques based on stock market returns. The empirical evidence is obtained by calculating cross-correlation coefficients of sectoral stock market returns with industrial production, by estimating a limited dependent variable model, and by setting up a trivariate structural vectorautoregression model including a stock market dispersion measure. The results suggest that the influence of sectoral shocks on the dynamics of real output is rather small.
Keywords: E44; E32; 330; real business cycles; sectoral shocks; stock market dispersion; probit model; structural VAR; Real Business Cycle; Strukturwandel; Produktivität; Schock; Börsenkurs; Rendite; Branche; Korrelation; VAR-Modell; Schätzung; Deutschland